Trends in Film Studies in the Context of Modern World Cinematography - Kopbayeva, G.K.; Nurpeis, B.K.; Eskendirov, N.R.; Gabdrashitova, K.A. (International Journal of Criminology and Sociology, 2022)
This article is devoted to the questions of the history of the Kazakh film studies development and further prospects in comparison with the dynamics of world film studies. The authors have analyzed the typical issues of film studies development in the Central Asia region, studied the specifics of film schools in five countries: Kazakhstan, Kyrgyzstan, Uzbekistan, Turkmenistan and Tajikistan. Conclusions have been drawn on the development of film studies in this region. Overall, the evaluation of development prospects, given in the conclusion of the study, can certainly have a beneficial impact on the development of the Kazakh films, its popularization in the world, and also help surmount potential obstacles in the way of its flourishing. The main objective of the survey is to demonstrate the regularities of utilizing the experience of international film schools in the national schools of film studies and focus on the similar means of development of the Kazakh and Russian film studies from Soviet times. Subsequently, Based on the research, the authors suggest practical measures to develop national film studies and its integration into world film studies.